1985
DOI: 10.1002/cne.902360304
|View full text |Cite
|
Sign up to set email alerts
|

Organization of the nigrothalamocortical system in the rhesus monkey

Abstract: The nigrothalamocortical connections and their topography were analyzed by autoradiography and double or triple retrograde labeling with the fluorescent dyes Fast Blue, Diamidino Yellow, and Propidium Iodide. Injections of tritiated leucine into different parts of the substantia nigra (SN) revealed that the medial SN projects to the medial magnocellular subdivisions of the ventral anterior (VAmc) and mediodorsal (MDmc) nuclei of the thalamus while the lateral SN projects to the more lateral and more posterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
206
3

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(227 citation statements)
references
References 36 publications
18
206
3
Order By: Relevance
“…Fourth, the other two regions of the presumptive motor thalamus, VM and VA, have only minor connections with areas of motor cortex, and their main functions may not be motor. These nuclei have connections with prefrontal cortex, FEF and pre-SMA in monkeys (Kunzle and Akert, 1977;Goldman-Rakic and Porrino, 1985;Ilinsky et al, 1985;Morel et al, 2005), and our injections in prefrontal cortex of galagos labeled these nuclei. In monkeys, projections from the substantia nigra to VA and VM (Macchi and Jones, 1997) implicate these nuclei in motor functions, although direct projections from VAmc and VM to motor areas of cortex in macaques are sparse.…”
Section: Discussionsupporting
confidence: 51%
“…Fourth, the other two regions of the presumptive motor thalamus, VM and VA, have only minor connections with areas of motor cortex, and their main functions may not be motor. These nuclei have connections with prefrontal cortex, FEF and pre-SMA in monkeys (Kunzle and Akert, 1977;Goldman-Rakic and Porrino, 1985;Ilinsky et al, 1985;Morel et al, 2005), and our injections in prefrontal cortex of galagos labeled these nuclei. In monkeys, projections from the substantia nigra to VA and VM (Macchi and Jones, 1997) implicate these nuclei in motor functions, although direct projections from VAmc and VM to motor areas of cortex in macaques are sparse.…”
Section: Discussionsupporting
confidence: 51%
“…These regions provide input to the anterior nuclei of the thalamus (Groenewegen et al 1990). The AV of the thalamus, which exhibits the highest expression of D 3 receptors within the thalamus, receives a nigrothalamic GABAergic innervation from the SNr (Ilinsky et al 1985), a region of relatively higher expression of D 3 and D 2 receptors. This provides multiple sites at which drugs such as antipsychotics might act to regulate activity in the "limbic" loop via interaction with the D 3 receptor.…”
Section: Resultsmentioning
confidence: 99%
“…The AV appears to represent a major site of interaction of the D 2 and D 3 receptors, because it possesses both types of binding sites in comparable concentrations as well as neurons expressing one or both mRNA species. The AV receives a nigrothalamic innervation from the SNr, a region of relatively higher expression of D 3 than D 2 receptors, via GABAergic nigrothalamic pathway (Ilinsky et al 1985;Kultas-Ilinsky and Ilinsky 1990), which may be originating from non-dopaminergic D 3 mRNA positive neurons frequently observed in SNr. The AV also receives massive projections from the MM through the mtt, the former enriched with D 3 mRNA and the latter with binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, anatomical tracings have shown that STN neurons project to SNr, which in turn target the DLPFC through the nigral-receiving area of thalamus. 147 Nonetheless, it seems plausible that GPi HFS could have antidromically activated STN projections collateralizing in both the GPi and the SNr and thus indirectly affected the DLPFC.…”
Section: Why So Many Targets?mentioning
confidence: 99%